Potensi Pengembangan Pariwisata Halal dan Pelestarian Kearifan Lokal Terhadap Pembangunan Ekonomi Daerah Tanjungpinang Kepri - Yanti, Mira Dama; Ramadhani, Dinda Suci; Abadi, Septriau Putra; Oktana , Enda; Iqbal, Muhammad (Bahtera Inovasi, 2026)
Due to the increased awareness of the need for sharia-compliant travel services among Muslims worldwide, the halal tourism trend has grown rapidly in recent years. Tanjungpinang has a lot of potential for the growth of halal tourism because of its natural riches and Islamic-based local knowledge. The goal of this study is to determine and evaluate the potential for halal tourism, the preservation of local knowledge, and their effects on the Tanjungpinang region's economic growth. This study employed descriptive qualitative analysis as its methodology, gathering data via observation, interviews, and documentation. Data reduction, data presentation, and conclusions are examples of data analysis approaches. The study's findings show that Tanjungpinang City has a great deal of potential for halal tourism growth, which is bolstered by the variety of tourist attractions, the facilities that are available, and the local knowledge of Islamic history and Malay culture. Although it hasn't spread equally yet, the incorporation of local knowledge into tourism-related activities has started. In terms of the economy, tourist growth boosts company activity, absorbs labor, and increases regional revenue. As a result, halal travel based on local knowledge is crucial to the growth of the local economy.